Solubility parameter‐based screening methods for early‐stage formulation development of itraconazole amorphous solid dispersions. (10th February 2016) - Piccinni, Piero; Tian, Yiwei; McNaughton, Alyn; Fraser, Jane; Brown, Stephen; Jones, David S.; Li, Shu; Andrews, Gavin P.
Abstract: Objectives: This article uses conventional and newly extended solubility parameter (δ) methods to identify polymeric materials capable of forming amorphous dispersions with itraconazole (itz). Methods: Combinations of itz and Soluplus, Eudragit E PO (EPO), Kollidon 17PF (17PF) or Kollidon VA64 (VA64) were prepared as amorphous solid dispersions using quench cooling and hot melt extrusion. Storage stability was evaluated under a range of conditions using differential scanning calorimetry and powder X‐ray diffraction. Key findings: The rank order of itz miscibility with polymers using both conventional and novel δ‐based approaches was 17PF > VA64 > Soluplus > EPO, and the application of the Flory–Huggins lattice model to itz–excipient binary systems corroborated the findings. The solid‐state characterisation analyses of the formulations manufactured by melt extrusion correlated well with pre‐formulation screening. Long‐term storage studies showed that the physical stability of 17PF/vitamin E TPGS–itz was poor compared with Soluplus and VA64 formulations, and for EPO/itz systems variation in stability may be observed depending on the preparation method. Conclusion: Results have demonstrated that although δ‐based screening may be useful in predicting the initial state of amorphous solid dispersions, assessment of the physical behaviour of the formulations at relevant temperatures may be more appropriate for the successful development of commercially acceptable amorphous drug products.